Find answers to your most challenging questions with the help of IDNLearn.com's experts. Our platform is designed to provide trustworthy and thorough answers to any questions you may have.


Given f(x) = 3x- 1 and 9(x) = 2x-3, for which value of
х
does g(x) = f(2)?

X= 3/2

X= 2

X= 5/2

X = 4


Sagot :

Answer:

x = 4

Step-by-step explanation:

[tex]f(x)=3x-1\\g(x)=2x-3[/tex]

substitute x = 2 into f(x):

[tex]f(2)=(3 \times2)-1=5[/tex]

equate g(x) with found value for f(2) and solve for x:

[tex]g(x)=f(2)\\2x-3=5\\2x=8\\x=4[/tex]

Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. IDNLearn.com is committed to your satisfaction. Thank you for visiting, and see you next time for more helpful answers.